STRENGTHENING THE MOBILE AD HOC NETWORKS USING ENHANCED SELF DETECTION ROUTING SCHEME - Ankita A. Mahamune; M. M. Chandane (ICTACT Journal on Communication Technology, 2022)
Reliable routing in Mobile Ad hoc NETwork (MANET) depends on individual node cooperation. The entire network performance may degrade because of even a single misbehaving node participating as an intermediate node. Thus, there is a need for incorporating secure routing with MANET to successfully operate in an adverse environment where routing security threats are employed. Looking at a few of the unsuccessful attempts by state-of-the-art routing schemes at certain applications, this paper proposes a trust-based secure routing termed as Enhanced Self-Detection Routing Scheme (ESDRS). This proposed scheme incorporates a self-detection procedure into a standard dynamic routing protocol Ad hoc On-Demand Distance Vector (AODV), finally resulting in detection and reaction to malicious nodes in MANET. The validation of the proposed approach is carried out through a comparative performance analysis with the recent Evolutionary Self-Cooperative Trust (ESCT) scheme and the standard AODV. The comparison is based on computations of Packet Delivery Ratio (PDR), delay, throughput, jitter, number of dropped data packets, Probability of Detection (PoD) of malicious and benevolent behavior, and normalized routing overhead while varying the number of nodes, the number of attackers, and node speed. Simulation results affirm that the proposed scheme improves the metric values as compared to the other routing schemes.